Innovative transcatheter procedures for the treatment of heart failure - Saia, Francesco (Cardiovasc Diagn Ther, 2021)
The prevalence of heart failure (HF) continues to rise over time, with aging of the population and increased survival of incident cases. Major improvements occurred in drug therapy but morbidity and mortality of HF patients remain high. Some non-pharmacologic approaches to HF are already part of standard treatment for HF, including implantable cardioverter-defibrillators, cardiac resynchronization therapy (CRT) and left ventricular assist devices (LVADs). A number of transcatheter treatments and devices have been developed to improve management of valvular heart diseases (VHD), and some of them are being used or tested in specific HF conditions. For example, transcatheter aortic valve implantation (TAVI) to unload the left ventricle in patients with moderate aortic stenosis (AS) and HF or TAVI for severe aortic regurgitation (AR) in patients with LVADs. Similarly, percutaneous mitral valve repair can be used to improve prognosis and quality of life in patients with functional mitral valve regurgitation, and has been proposed as a bridge-to-LVAD or to heart transplant in selected patients. Other devices have been specifically developed for the treatment of chronic HF. In this review we describe the main devices used in the treatment of HF associated with aortic and mitral valve disease, as well as novel transcatheter interventions for chronic HF with different pathophysiologic targets.